An Inverse Method to Obtain Porosity, Fibre Diameter and Density of Fibrous Sound Absorbing Materials - ALBA, Jesus; del REY, Romina; RAMIS, Jaime; ARENAS, Jorge P. (Archives of Acoustics, 2011)
Characterization of sound absorbing materials is essential to predict its acousticbehaviour. The most commonly used models to do so consider the flow resistiv-ity, porosity, and average fibre diameter as parameters to determine the acousticimpedance and sound absorbing coefficient. Besides direct experimental techniques,numerical approaches appear to be an alternative to estimate the material’s pa-rameters. In this work an inverse numerical method to obtain some parameters ofa fibrous material is presented. Using measurements of the normal incidence soundabsorption coefficient and then using the model proposed by Voronina, subsequentapplication of basic minimization techniques allows one to obtain the porosity, aver-age fibre diameter and density of a sound absorbing material. The numerical resultsagree fairly well with the experimental data.